New N-acyl amino acid-functionalized biodegradable polyesters for pharmaceutical and biomedical applications - Taresco, Vincenzo; Suksiriworapong, Jiraphong; Styliari, Ioanna D.; Argent, Richard H.; Swainson, Sadie M.E.; Booth, Jonathan; Turpin, Eleanor R.; Laughton, Charles A.; Burley, Jonathan C.; Alexander, Cameron; Garnett, Martin C. (Royal Society of Chemistry, 2016)
A novel class of biodegradable polyesters has been generated by coupling poly(glycerol adipate) with N-acyl aromatic amino acids. This new set of polymers from this highly versatile polymeric platform may offer unprecedented new opportunities to produce biodegradable and biocompatible polymers with tailorable physical–chemical properties.